2017
DOI: 10.1002/anie.201708127
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phenalenyl‐Fused Pyrylium Cations: Divergent C−H Activation/Annulation Reaction Sequence of Naphthalene Aldehydes with Alkynes

Abstract: Described herein is the synthesis of stable oxonium-doped polycyclic aromatic hydrocarbons (PAHs) by the rhodium-catalyzed C-H activation/annulations of naphthalene-type aldehydes with internal alkynes. This protocol provides four divergent reaction types, including two unexpected annulations with an oxygen transposition process, which lead to diverse types of phenalenyl-fused pyrylium cations comprising a four-, five-, or six-ring-fused π-conjugated core. The annulations exhibit an exquisite regioselectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 45 publications
1
50
0
Order By: Relevance
“…The 19 FNMR spectrum and X-ray single-crystal diffraction indicated that this oxonium-doped PA Hc ontains SbF 6 À as the counteranion. [18] With this consideration in mind, two equivalents of NaSbF 6 were added, thus dramatically improving the yield of 3aa to 38 % (Table S1, entry 3). Further optimization of reaction parameters,such as solvent, oxidant, reaction temperature and time, improved the yield of 3aa to 77 %(Table S1, entry 14).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The 19 FNMR spectrum and X-ray single-crystal diffraction indicated that this oxonium-doped PA Hc ontains SbF 6 À as the counteranion. [18] With this consideration in mind, two equivalents of NaSbF 6 were added, thus dramatically improving the yield of 3aa to 38 % (Table S1, entry 3). Further optimization of reaction parameters,such as solvent, oxidant, reaction temperature and time, improved the yield of 3aa to 77 %(Table S1, entry 14).…”
mentioning
confidence: 99%
“…As shown, the annulation of naphthalene aldehyde allows awide scope of alkynes,thus producing afamily of four-ring-fused phenalenyl-based pyrylium cations.T he reactions of symmetrical diaryl alkynes with electron-donat-ing groups such as p-methyl, m-methyl, p-methoxy,a nd 2naphthyl smoothly occurred in 55, 69, 67, and 90 %y ields, respectively (3ab-ae). [18] Thed iaryl alkynes bearing an electron-withdrawing group such as fluoro,c hloro,C F 3 , CO 2 Et, and CHO were also be tolerated (3af-aj). 4-Phenylsubstituted a-naphthaldehyde gave 3ea in 72 %yield.…”
mentioning
confidence: 99%
See 3 more Smart Citations